Heavy Metal Pollution and Potential Ecological Risk Assessment in a Typical Mariculture Area in Western Guangdong - Ning He (MDPI AG, 2021)
The distribution characteristics, environmental contamination states, and potential ecological risks of chromium (Cr), copper (Cu), arsenic (As), lead (Pb), and cadmium (Cd) in seawater, sediment and breeding feed were studied in a typical mariculture area in western Guangdong of China. Pearson correlation analysis was used to determine metal homology, and the single-factor index, potential ecological risk index, hazard quotient (HQ), and joint probability curve (JPC) were used to evaluate pollution states and ecological risk of metals. Four main statements can be concluded from the results: (1) Pb and Cu showed a similar distribution pattern in the seawater and sediment and their contents in the breeding wastewater exceeded the standard limits in several stations. (2) Cr, Cu, and As have similar sources in the feeds, which may be an important source of metals in water. (3) The risk assessment revealed that the sediment from the studied areas was at a low ecological risk of heavy metal, whereas, water in the pond and outfall was slightly polluted by Pb, and water in the cages and outfall were slightly polluted by Cu. (4) Both the hazard quotient (HQ) and joint probability curve showed the overall risk probabilities (ORPs) in the waters ranked as Cu > Cr > Pb > Cd > As. Although Pb and Cd had HQ values greater than 1, their ORPs were acceptable. This study highlights that multiple evaluation models are more reliable than the single ecological risk assessment for evaluating heavy metal pollution risks in the mariculture area.